Public Preferences for Pasture Landscapes and the Role of Scale Heterogeneity - Henning Schaak; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2021)
The paper investigates the influence of different model specifications for interpreting the results of discrete choice experiments when investigating heterogeneous public landscape preferences. Comparing model specifications based on the Mixed Multinomial Logit and the Generalized Multinomial Logit Model reveals that the parameter estimates appear qualitatively comparable. Still, a more in-depth investigation of the conditional estimate distributions of the sample show that parameter interactions in the Generalized Multinomial Logit Model lead to different interpretations compared to the Mixed Multinomial Logit Model. This highlights the potential impact of common model specifications in the results in landscape preference studies.
Keywords: 330; discrete choice experiment; public landscape prefer-ences; livestock; Mixed Multinomial Logit Model; Generalized Multinomial Mixed Logit Model